Whey Proteins and Bioactive Peptides: Advances in Production, Selection and Bioactivity Profiling - Anna Luparelli; Daniela Trisciuzzi; William Matteo Schirinzi; Leonardo Caputo; Leonardo Smiriglia; Laura Quintieri; Orazio Nicolotti; Linda Monaci (Biomedicines)
The whey protein (WP) fraction represents 18–20% of the total milk nitrogen content. It was originally considered a dairy industry waste, but upon its chemical characterization, it was found to be a precious source of bioactive components, growing in popularity as nutritional and functional food ingredients. This has generated a remarkable increase in interest in applications in the different sectors of nutrition, food industry, and pharmaceutics. WPs comprise immunoglobulins and proteins rich in branched and essential amino acids, and peptides endowed with several biological activities (antimicrobial, antihypertensive, antithrombotic, anticancer, antioxidant, opioid, immunomodulatory, and gut microbiota regulation) and technological properties (gelling, water binding, emulsification, and foaming ability). Currently, various process technologies and biotechnological methods are available to recover WPs and convert them into BioActive Peptides (BAPs) for commercial use. Additionally, in silico approaches could have a significant impact on the development of novel foods and/or ingredients and therapeutic agents. This review provides an overview of current and emerging methods for the production, selection, and application of whey peptides, offering insights into bioactivity profiling and potential therapeutic targets. Recent updates in legislation related to commercialized WPs-based products are also presented.